Biosynthesis of versatile PHA copolymers by thermophilic members of the genus Aneurinibacillus - Rehakova, Veronika; Pernicova, Iva; Kourilova, Xenie; Sedlacek, Petr; Musilova, Jana; Sedlar, Karel; Koller, Martin; Kalina, Michal; Obruca, Stanislav (International journal of biological macromolecules, 2023)
Thermophilic members of the genus Aneurinibacillus constitute a remarkable group of microorganisms that exhibit extraordinary flexibility in terms of polyhydroxyalkanoates (PHA) synthesis. In this study, we demonstrate that these Gram-positive bacteria are capable of the utilization of selected lactones, namely, γ-valerolactone (GVL), γ-hexalactone (GHL), and δ-valerolactone (DVL) as the structural precursors of related PHA monomers. In the presence of GVL, a PHA copolymer consisting of 3-hydroxybutyrate, 3-hydroxyvalerate, and also 4-hydroxyvalerate was synthesized, with a 4 HV fraction as high as 53.1 mol%. Similarly, the application of GHL resulted in the synthesis of PHA copolymer containing 4-hydroxyhexanaote (4HHx) (4HHx fraction reached up to 11.5 mol%) and DVL was incorporated into PHA in form of 5-hydroxyvalerate (5 HV) (maximal 5 HV content was 44.2 mol%). The produced materials were characterized by thermoanalytical and spectroscopic methods; the results confirmed extremely appealing material properties of produced copolymers. Further, due to their unique metabolic features and capability of incorporating various PHA monomers into the PHA chain, thermophilic Aneurinibacillus spp. can be considered not only promising chassis for PHA production but also potential donors of PHA-relevant genes to improve PHA production in other thermophiles by using approaches of synthetic biology.
Keywords: Polyesters; polyhydroxyalkanoáty; Fermentation; Copolymers; Thermophiles; Aneurinibacillus spp.; polyestery; Lactones metabolization; Polyhydroxyalkanoates; fermentace; Bacillales